Whole genome sequencing and annotation of Daedaleopsis sinensis, a wood-decaying fungus significantly degrading lignocellulose - Ma, Jin-Xin; Wang, Hao; Jin, Can; Ye, Yi-Fan; Tang, Lu-Xin; Si, Jing; Song, Jie (Frontiers in Bioengineering and Biotechnology, 2024)
Daedaleopsis sinensis is a fungus that grows on wood and secretes a series of enzymes to degrade cellulose, hemicellulose, and lignin and cause wood rot decay. Wood-decaying fungi have ecological, economic, edible, and medicinal functions. Furthermore, the use of microorganisms to biodegrade lignocellulose has high application value. Genome sequencing has allowed microorganisms to be analyzed from the aspects of genome characteristics, genome function annotation, metabolic pathways, and comparative genomics. Subsequently, the relevant information regarding lignocellulosic degradation has been mined by bioinformatics. Here, we sequenced and analyzed the genome of D. sinensis for the first time. A 51.67-Mb genome sequence was assembled to 24 contigs, which led to the prediction of 12153 protein-coding genes. Kyoto Encyclopedia of Genes and Genomes database analysis of the D. sinensis data revealed that 3831 genes are involved in almost 120 metabolic pathways. According to the Carbohydrate-Active Enzyme database, 481 enzymes are found in D. sinensis, of which glycoside hydrolases are the most abundant. The genome sequence of D. sinensis provides insights into its lignocellulosic degradation and subsequent applications.